The Effect of External Pressure, Management Commitment and Accessibility towards Transparency of Financial Reporting - Bambang Jatmiko; Muhammad Budi Setiawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research Aims: This study aims to examine and empirically prove the Effects of External Pressure, Management Commitment, and Accessibility of Financial Statements on Transparency of Financial Reporting in Regional Work Units in Yogyakarta City.Design/Methodology/Approach: The methodology used is survey with purposive sampling. The respondents of this study consists of 74 people. The analytical tool used in this study is multiple linear regression using the SPSS.Research Findings: The test results indicate that external pressures, management commitment, and accessibility of financial statements have a positive effect on financial reporting transparency.Theoretical contribution/Originality: this research filled the research gap related to the issue of determinants of transparency of financial reporting in local governments which has got minimal attention from researchers.Practitioner/Policy implication: departing from the results of this study, it is recommended to increase the transparency of financial reporting, external pressure, management commitment and accessibility must be encouraged.Research limitation/Implication: This research was only conducted in the city of Yogyakarta, so it has weak external validity. The generalization of this study results does not represent a broader scope.